Rasio Pembayaran Dividen pada Subsektor Industri Pariwisata, Hotel, dan Restoran Tahun 2013-2017 - Muhammad Ikhlas Dharma; Bambang Hermanto; Dian Fordian (Jurnal Akuntansi Keuangan dan Bisnis, 2020)
The foreign tourists in Indonesia has grown almost twice and the local tourist reached approxiamately 20 million in 2017. The increasing number of visits will obviously contribute to Indonesia economy. This research aims to determine the impact of cash ratio, debt to equity ratio, and return on assets on dividend payout ratio in Indonesian tourism, hotel, and restaurants industry within the period of 2013-2017. The sample in this research includes five five companies meeting the criteria. The companies were selected using purposive sampling technique and research data were analyzed using panel data regression. The results indicate that cash ratio, debt to equity ratio, and return on assets have a significant influence on dividend payout ratio simultaneously. The cash ratio has a positive effect on dividend payout ratio partially, while debt to equity ratio and return on assets have a negative effect on dividend payout ratio.